Resource supply governs the apparent temperature dependence of animal production in stream ecosystems. (1st October 2020) - Junker, James R.; Cross, Wyatt F.; Benstead, Jonathan P.; Huryn, Alexander D.; Hood, James M.; Nelson, Daniel; Gíslason, Gísli M.; Ólafsson, Jón S.
Abstract: Rising global temperatures are changing how energy and materials move through ecosystems, with potential consequences for the role of animals in these processes. We tested a central prediction of the metabolic scaling framework—the temperature independence of animal community production—using a series of geothermally heated streams and a comprehensive empirical analysis. We show that the apparent temperature sensitivity of animal production was consistent with theory for individuals ( E pind = 0.64 vs. 0.65 eV), but strongly amplified relative to theoretical expectations for communities, both among ( E pamong = 0.67 vs. 0 eV) and within ( E pwithin = 1.52 vs. 0 eV) streams. After accounting for spatial and temporal variation in resources, we show that the apparent positive effect of temperature was driven by resource supply, providing strong empirical support for the temperature independence of invertebrate production and the necessary inclusion of resources in metabolic scaling efforts. Abstract : We tested a central prediction of the metabolic scaling framework—the temperature independence of animal community production—using a series of geothermally heated streams and a comprehensive empirical analysis. After accounting for spatial and temporal variation in resources, we show that the apparent positive effect of temperature was driven by resource supply, providing strong empirical support for the temperature independence of invertebrate production and the necessary inclusion of resources in metabolic scaling efforts.